Pengaruh model pembelajaran project based learning terhadap keterampilan menulis karangan narasi - Khafifah, Umy; Wardana, Aditya Eska; Triana, Putri Meinita (Borobudur Educational Review, 2024)
This research aims to determine the effect of the Project Based Learning learning model on narrative essay writing skills in class IV students at SD Negeri Mertoyudan 3. This research uses the Pre-Experimental Design research type with the One-Group Pretest-Posttest Design model. This research uses non-probability sampling techniques. The sample in this study was class IV students at SD Negeri Mertoyudan 3, totaling 20 students. The data collection method was carried out using performance tests and observation. Swimmer analysis test using the normality test. Data analysis uses parametric statistical techniques, namely the Paired Sample T-Test with the help of the IBM SPSS Statistics 25 application. The results of the research show that there is an increase in the average student score with a pretest average of 67 and a posttest average of 82. Based on the Paired results Sample T-Test produces a sig value. 0.000 < 0.05, meaning that the application of the Project Based Learning model has a significant effect on narrative essay writing skills in class IV students at SD Negeri Mertoyudan 3.